2018
DOI: 10.1016/j.artd.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A dedicated anticoagulation clinic does not improve postoperative management of warfarin after total joint arthroplasty

Abstract: BackgroundPeriprosthetic joint infections (PJIs) are devastating complications. Excessive anticoagulation with warfarin is an independent risk factor for PJIs. The use of a dedicated anticoagulation clinic to improve warfarin management has not been proven.MethodsBetween 2006 and 2014, we identified 92 patients who were placed on postoperative warfarin, and later developed PJI. These patients were compared to 313 patients who underwent total joint arthroplasty placed on warfarin without developing PJI. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…В настоящее время варфарин для первичной профилактики тромбозов и тромбоэмболий после выполнения ЭТС и ЭКС применяется редко. Данные о его назначении описаны лишь в немногочисленных исследованиях [41][42][43][44]. В представленных работах варфарин не продемонстрировал преимущества, и его применение было связано с большим риском развития кровотечений и осложнений.…”
Section: фармакологическая профилактика втэunclassified
“…В настоящее время варфарин для первичной профилактики тромбозов и тромбоэмболий после выполнения ЭТС и ЭКС применяется редко. Данные о его назначении описаны лишь в немногочисленных исследованиях [41][42][43][44]. В представленных работах варфарин не продемонстрировал преимущества, и его применение было связано с большим риском развития кровотечений и осложнений.…”
Section: фармакологическая профилактика втэunclassified
“…35 Additionally, patient compliance and laboratory monitoring programs have also come under scrutiny with regard to improving the efficacy, and the safety profiles of using warfarin as the principal chemoprophylaxis following total joint arthroplasty. 36,37 Cho et al reported equal efficacy with improved bleeding risks using lower dose of warfarin (lower international normalized ratio: INR= 1.5 to 2.5) over a four week course. 38 There is increasing evidence-based data supporting the use of aspirin following total joint arthroplasty.…”
Section: Where Have We Been?mentioning
confidence: 99%